Comparison of space-frequency pre-filtering techniques and space-frequency block coding for DL MC-CDMA Systems - Silva, Adão
This paper aims to compare the performance of the different transmit signal design techniques that have been proposed recently for DL MC-CDMA systems and presents a joint space-frequency multi-user pre-filtering and spreading scheme. We consider the use of antenna arrays at the base station (BS) and a single antenna at the mobile terminal (MT) and derive the proposed multi-user space-frequency pre-filtering technique that formats the transmitted signals to eliminate the effects of multiple access interference (MAI) and channel distortions at the mobile terminals, whilst maintaining low MT complexity. Thus, two types of detectors are considered at the MT: simple despreading and single user equalizers. The performance of the different schemes is evaluated, considering either perfect or nonperfect CSI and channel coding based on UMTS specifications, in order to select the best strategy for DL TDD MC-CDMA systems. © 2006 IEEE.